Internal Endpoint Cooking Temperature Alters Quality and Consumer Acceptability of Pork Loin Chops - Savannah L. Douglas; Ricardo J. Barrazueta-Coredero; Gabriela M. Bernardez-Morales; Nina E. Gilmore; Linda S. Barahona-Dominguez; Sungeun Cho; Jason T. Sawyer (Foods, 2025)
Quality and consumer satisfaction of meat products could be influenced by endpoint cooking temperatures. Attributes of pork, such as palatability, cooking loss, and internal color, influence consumer acceptability. The degree of doneness was evaluated on pork chop characteristics of texture, cooking loss, consumer acceptability, and electronic nose. Pork loin chops (N = 264) were allocated randomly to one of three endpoint degrees of doneness (63 °C, 71 °C, and 79 °C). Cooking pork chops to an internal temperature of 79 °C caused the cooked color to be darker (p < 0.0001) and less red (p = 0.0057). In addition, chops cooked to a 63 °C degree of doneness had greater moisture and lower shear force values (p < 0.0001). Consumer panel ratings of flavor profiles were greater for juiciness, texture, and tenderness (p < 0.0001) when chops were cooked to a 63 °C degree of doneness. Electronic nose analysis of the changes in cooked volatiles can impact the overall flavor and aroma profiles of pork loin chops. These findings conclude that cooking pork chops to an internal temperature of 63 °C improves the overall eating quality, acceptability, and cooking characteristics of pork loin chops. However, more information on the use of an optimal endpoint cooking temperature is needed to improve consumer awareness of pork chop quality.